ChemInform Abstract: A6U3Sb2P8S32 (A: Rb, Cs): Quinary Uranium(IV) Thiophosphates Containing the [Sb(PS4)3]6— Anion. Issue 24 (2nd June 2014) - Babo, Jean‐Marie; Diefenbach, Kariem; Albrecht‐Schmitt, Thomas E.
Abstract The title compounds are prepared from stoichiometric mixtures of Sb, M2S3 (M: Rb, Cs), U, and P2S5 (silica tubes, 500 °C, 5 d 50% yield) and characterized by single crystal XRD, solid state UV/VIS/NIR and Raman spectroscopy, and magnetic measurements.